Sistem Pakar Diagnosa Gangguan Kecemasan Pada Difabel Menggunakan Metode Forward Chaining Berbasis Web - Larasaty, Raditha; Prasetyaningrum, Putri Taqwa (Journal of Computer and Information Systems Ampera, 2024)
Anxiety disorders are a mental health condition that can disrupt the quality of life of people with disabilities. This research aims to create a web-based expert system for Gumregah Management in Argorejo Village to facilitate early diagnosis and treatment of anxiety disorders. With limited access to specialist doctors, the system uses the Forward Chaining method to ensure easy and accurate diagnosis. Test results showed 100% accuracy from 15 patients, confirming the system's effectiveness in treating anxiety disorders in people with disabilities in areas with limited access to mental health services. This research contributes to solutions for diagnosing and providing early treatment of anxiety disorders in people with disabilities.